KOMITMEN PEMERINTAH DAERAH TERHADAP PEMBANGUNAN DI BIDANG PENDIDIKAN DALAM ERA OTONOMI DAERAH : Studi Kasus Kebijakan Publik di Kabupaten dan Kota Bekasi - Enap, Agus (2013)
The paradigm of the educational management in a decentralization appears systemic changes to the available institutions. The design of the educational organization constitutes an implementation of various perceptionts of the authority submitted by the eental goverenment. In the level of the educational problem concepts by the regional goverenment has become a serious attention, nevertheless in the implementation level has not been balancing or still for from the hope. For it still occurs inefficiency and ineffectivity in the management of education like too fat in the organication of educational management. The competencies of the goverenment apparattur are still low, this case is caused by the placement and appointment of the staff to place the structural positions has not owned the working prames v .th the measured indicators about the working achievement and the placement of the staf has not wholly used a concept to fulpill the skill requirements and their fields. Besides it is not based on the clear rewards become the rewards themseloes in the management of the civil sevants' officialdom have not existed clearly. About the budget of education becomes the respons ibility of the regional goverenment. The budget support to conduct the education has not shown the fair and efficient budget. This is caused not to be existed a standardized formulation and agreed to account the amount of the budget allocation to the educational sector which reflects the real needs. The budget for education commulativel showed a significant increasement but the incerasement has not shown the real needs, for the increasement of budget is nearly 90% to pay the salaries of the staff. Whereas to spend for the educational sector development has not achieved the first rank but it is still in the third rank, nomely around 6 - 17% from the number of the development budget or around 3 - 7% from the amount of the regional budget (APBD). Rather directly or indirectly the aboved condition much effects to the working ability of the educational sector in wich it can imply to the educational quality incerasement itself.